PERENCANAAN MESIN PENGEROLL LAPISAN SANDAL MENGGUNAKAN MOTOR LISTRIK DENGAN SISTEM SEMI-OTOMATIS SKALA HOME INDUSTRY - Muhamad Fatoni (Jurnal Teknik Mesin, 2019)
In the current era, the development of technology has helped many people, especially to facilitate the work that arises in life with new discoveries in the field of technology. Permaslahan which often arises in the process of rolling the slipper layer is still using manual or human power systems, which are less effective and can take time which is old. Therefore, the authors make "Planning the flip-liner bending machine using an electric motor with an automatic scale home industry system" Which serves to process the rollers with a relatively short time by not consuming too much human power, the roll material is EVA sponge rollers, bending machines This flip layer fulfills household electricity as a source of driving force, how the work of the flip lining machine with this automatic system that is after the electric motor switch is turned on, the system will automatically turn on, if there are workers close to the engine, then the motor rotation will rotate the pulleys and transmission belts, and move the pulleys on the roll which causes the shaft to rotate, the shaft will rotate the rollers attached to the shaft. From the results of the analysis and calculation of engine planning, the specifications of each component found on the engine are obtained, such as the electric motor used is 0.5 HP with a motor rotation speed of 1400 rpm. The number of roll 2 with a diameter of 90 mm and a length of 350 mm, pulley motor 80 mm and pulley shaft 400 mm, for shaft material with a diameter of S30C 40 mm. For belts use type A belt V No. 48. The bearing used is the type of rolling bearing with number 6002. For the dimensions of this tool is the length of 450 mm, width of 550 mm, and height of 900 mm. Engine capacity in 1 score is 50 seconds.                                                                                Keywords : flip layer, pengeroll machine, automatic system, electric motor